2004
DOI: 10.1007/978-3-662-08729-9
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of Steels and Cast Irons

Abstract: How many times ha ve 1 heard the question MIs there stIll anything to discover in steels ?~ often with the conclusive comment '~know everything about steelsthey've been studied lor years !" On the contrary, in recent decades, the development 01 new grades, extended lunctions and novel applications has continued at an accelerating pace. More than hali the steels used today did not even exist live years ago.This simply demonstrates the vast potential 01 these materials. Starting Irom an iron base, numerous alloy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0
23

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 0 publications
5
60
0
23
Order By: Relevance
“…2. The resultant microstructure is typical for the conventional gray cast irons in comparison with other studies [2][3][4][5][6][7][8]. Indeed, the appearance of three predominant structures that characterize the gray cast iron with lamellar graphite is highlighted by our observations, these are:…”
Section: Resultssupporting
confidence: 80%
“…2. The resultant microstructure is typical for the conventional gray cast irons in comparison with other studies [2][3][4][5][6][7][8]. Indeed, the appearance of three predominant structures that characterize the gray cast iron with lamellar graphite is highlighted by our observations, these are:…”
Section: Resultssupporting
confidence: 80%
“…Shear transformations often result in the formation of a new lattice orientation, resulting in a new crystallographic phase and phase interfaces. The transition between different phases is traditionally martensitic implying that no diffusion or local changes in chemistry should [33]. Mathew et al [19] has recently shown the effect of SIT on the corrosion response of CoCr supporting findings by Montero-Ocampo et al [21].…”
Section: Fig 18mentioning
confidence: 72%
“…They can easily replace each other during solidification and do not change the molecular structure of carbides. So these carbides are designated as multi-component compounds (Fe, Cr) 7 C 3 and (Fe, Cr) 3 C, which abbreviated are M 7 C 3 and M 3 C [21,22] . Figure 4 gives the SEM images of the metallurgical structure of the ATZ ceramic particle reinforced gray iron matrix surface composites.…”
Section: Composite Characterization and Testingmentioning
confidence: 99%